Handbook of education policy research [ - Ford, Timothy G.; Plank, David Natha , 1954-; Schneider, Barbara L. (Routledge ;[Washington, DC] : American Educational Research Association, 2009)
Educational policy continues to be of major concern. This AERA-sponsored Handbook presents two themes of defining the theoretical boundaries and methodological approaches of education policy research